THE THEORY, METHODOLOGY AND FEATURES OF BANKING PRODUCTS (World Economics and Finance Bulletin, 2022)
The analysis of approaches to the definition of the main categories of banking products has been carried out. The article is devoted to the analysis of new types of banking products and the features of their creation, as well as the study of banking strategies for promoting new products and services on the market. The main approaches of Russian, local and foreign authors in defining the concept of "banking product" are considered
Keywords: Banking product; banking operation; transaction; banking service